Algal Polysaccharides‐Based Nanoparticles for Targeted Drug Delivery Applications. (12th May 2022) - Zhang, Shuangshuang; Qamar, Sarmad Ahmad; Junaid, Muhammad; Munir, Bushra; Badar, Qurratulain; Bilal, Muhammad
Abstract: A huge variety of polysaccharides can be obtained from algal biomass having several attractive properties such as cost‐effectiveness, non‐toxicity, biodegradability, abundant availability, and biocompatibility. In recent years, algal polysaccharides (including alginates, carrageenans, fucoidans, ulvans, and agaroses) have extensively been reported for their chemical properties and important bioactive potentialities. Furthermore, algal polysaccharides have gained huge scientific interest as they are a significant source of biologically active compounds, and they show various medical potentialities including anticancer, antiproliferative, anticoagulant, antitumoral, and antiviral properties. Exceptional physicochemical and biological characteristics make them interesting candidates for biotechnological and biomedical investigations. In this review, nanodrug delivery systems based on different algal‐polysaccharides (alginates, carrageenans, fucoidan, ulvan, and other) are described in a systematic way. Moreover, the current challenges and future prospects in the area of algal exploitation for biomedical applications are summarized at the end. Abstract : Algal polysaccharides‐based nanoparticles provide versatile platforms for the delivery of therapeutic drug molecules with superior characteristics over conventional delivery routes, including controlled release, less/no side effects, cost‐effectiveness, biocompatibility, and high physiological stability.